Revolution in penology: rethinking the society of captives - Arrigo, Bruce A. (Rowman & Littlefield Publishers, 2010)
From constitutive criminology to constitutive penology -- Constitutive penology : critique of modernist philosophies of punishment -- The phenomenology of penal harm : on the criminology of the shadow and the stranger -- Constitutive penology and the pains of imprisonment -- The shadow and stranger in constitutive penology : on (dis)identities and (dis)continuities -- Conclusion: Sustaining the revolution in penology